Pengaruh Kecemasan Matematika terhadap Minat Belajar Siswa Sekolah Dasar - Jannah, Silfha Al; Sani, Mutia Intan; Fitri, , Mita Triana (Lembaga Yasin AlSys, 2024)
This type of research is descriptive quantitative research which aims to determine whether or not there is an influence of mathematics anxiety on the interest in learning of elementary school students in Jambi City. With a population and research sample of students from elementary schools in Jambi City. The instrument used in this research is a non-test instrument in the form of a questionnaire consisting of a mathematics anxiety questionnaire and a student interest in learning questionnaire, totaling 10 questions from each questionnaire. The questionnaire is a closed direct questionnaire, which means alternative answers are available in the questionnaire, so respondents only need to choose one answer that suits their condition. The initial hypothesis of this research is